Microstructure and photoluminescence of Eu-doped Sr3Al2O6 phosphors calcined with and without H3BO3 flux - Hong, Ji Ho; Lee, Ja Yeon; Kang, Ji Ho; Lee, Joon Yup; Jang, Ho Seong; Cho, Seong-Yong; Kim, Dong Hun (Pergamon Press Ltd., 2022)
The development of highly efficient and stable red phosphors fabricated using cost-effective and simple mass -production methods is essential for applications in future displays and lighting devices. Herein, we investigate the phase formation, microstructures, and luminescence properties of Sr3Al2O6:Eu powders synthesized using a solid-state reaction process. Single-phase Sr3Al2O6:Eu phosphors exhibiting excellent photoluminescence with color-tunable orange-red and red colors under different excitation wavelengths were successfully synthesized. The optimal Eu doping concentration of Sr3Al2O6, yielding strong photoluminescence with phase stability, was 5 at. %, with the concentration quenching point determined by systematic exploration. The addition of H3BO3 as a flux significantly affected the grain size and improved the emission intensity of the synthesized (Sr0.95Eu0.05)3Al2O6 phosphors up to 12.5 wt %, while secondary phases were formed at higher flux concen-trations. The photoluminescence intensities of the 5D0 -> 7F1 and 5D0 -> 7F2 transitions of 12.5 wt % H3BO3 added (Sr0.95Eu0.05)3Al2O6 increased by 3.4 and 4.2 times compared with the flux-free powders under the 394 nm-wavelength excitation, while the decay time decreased from 7.35 to 5.40 ms. Our report of the enhanced pho-toluminescence intensity and shortened decay time of (Sr0.95Eu0.05)3Al2O6 phosphors following the flux addition is promising for production of single-phase phosphors emitting multi-colors, which is needed for optical devices activated by various excitation frequencies.